METODE PENTARJIHAN MASLAHAH DAN MAFSADAH DALAM HUKUM ISLAM SEMASA - Ahmad, Ridzwan (Jurnal Syariah, 2008)
The concept of maslahah and mafsadah are always being used as a guide by Muslim Scholars to resolve contemporary Muslims problems. Although, the both concepts were discussed in Usul Fiqh’s books, the discussions only touch on a general concept based on examples from the existing Islamic Jurisprudence laws. Furthermore, how to apply the both concepts when there is a contradiction between the two is only been discussed in general without any specific method. This article tries to propose several ‘tarjih’ methods towards mafsadah and maslahah in resolving contemporary Muslim problems. The methods will be analyzed and used in order to ensure the application of maslahah and mafsadah are not derailed from the truth and is not easily used by certain bodies to claim that their decision is related with the both concepts.